Evaluation of the diagnostic performance of Alpha-1-Antitrypsin in early detection of hepatocellular carcinoma: Early detection of hepatocellular carcinoma - Sultan, Mohammed Q.; Charfeddine, Bassem; Hussain Al-Salih , Aws Rassul (Cellular and Molecular Biology, 2023)
Hepatocellular carcinoma (HCC) constitutes one of the most frequent cancer types and accounting the vast majority of tumour-related fatalities worldwide. HCC is remain related to a bad prognosis in patients with an advanced disease stage. This study was conducted to evaluate the relationship between A1AT concentration, A1AT gene promoter methylation, and A1AT genotype variation, and HCC risk. In this case-control research, we investigated A1AT levels in plasma as a diagnostic biomarker for the earlier detection of HCC in 100 patient samples. We also checked DNA promoter methylation of the A1AT gene, and genotypes in all the studied groups. The levels of AFP and A1AT in plasma were determined using ELISA and nephelometric techniques, respectively. The genomic DNA extracted from blood samples has been examined for S and Z genotypes using the PCR-RFLP technique, as well as gene A1AT promoter methylation was assessed by methylation specific-PCR assay.The plasma data analysis showed that there was a significant difference between HCC and healthy control samples regarding the level of AFP and A1AT. The range of plasma A1AT concentration was 166.6±27.28g/L in patients and 129.8±15.87g/L in controls (p <0.001). A1AT concentration was also associated with progressive tumour stages. Moreover, the roc curve stated that A1AT concentration is better in sensitivity than using AFP in early detection of HCC cancer patients as A1AT concentration at 135mg/L, had a sensitivity of 99% and a specificity of 79% for distinguishing cancer patients from healthy individuals. We concluded that the plasma A1AT concentration has higher sensitivity than AFP for early detection of HCC.